2011
DOI: 10.1140/epjb/e2011-20661-4
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the thermally induced austenitic phase transition in NiTi nanoparticles

Abstract: The reverse martensitic ("austenitic") transformation upon heating of equiatomic nickel-titanium nanoparticles with diameters between 4 and 17 nm is analyzed by means of molecular-dynamics simulations with a semi-empirical model potential. After constructing an appropriate order parameter to distinguish locally between the monoclinic B19 ′ at low and the cubic B2 structure at high temperatures, the process of the phase transition is visualized. This shows a heterogeneous nucleation of austenite at the surface … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 32 publications
3
59
2
Order By: Relevance
“…This difference is mainly due to size effects and consideration of the single crystal (in the simulations) vs. the polycrystalline (in the experiment) NiTi SMA samples; this is addressed in detail in the following sections. Significant size effects have been reported extensively, [25,27,28,30,61] where it is also demonstrated that the presence of defects such as free surfaces can appreciably alter the martensite transformation start Size effects are demonstrated in Figure 3 and some relevant results (evolution of microstructure at different temperatures and sizes) are documented in the supplementary material. Figure 3 shows the variation of martensite phase fraction with respect to temperature for different size of NiTi films.…”
Section: Figure-2mentioning
confidence: 81%
See 1 more Smart Citation
“…This difference is mainly due to size effects and consideration of the single crystal (in the simulations) vs. the polycrystalline (in the experiment) NiTi SMA samples; this is addressed in detail in the following sections. Significant size effects have been reported extensively, [25,27,28,30,61] where it is also demonstrated that the presence of defects such as free surfaces can appreciably alter the martensite transformation start Size effects are demonstrated in Figure 3 and some relevant results (evolution of microstructure at different temperatures and sizes) are documented in the supplementary material. Figure 3 shows the variation of martensite phase fraction with respect to temperature for different size of NiTi films.…”
Section: Figure-2mentioning
confidence: 81%
“…Detailed description of the different parameters is provided in [30] , respectively [30]. Such distribution for the order parameter arises primarily from the effects of thermal expansion or contraction on the bond length of the phases at different temperature.…”
mentioning
confidence: 99%
“…Fig. 1 shows all these structures resulting from the model potential, together with an order parameter χ, which is calculated out of the nearest neighbor environment of each atom [25]. Due to the shear in the monoclinic B19 ′ structure, two nearest neighbor lengths are elongated about 13.5% compared to the other six, denoted by a dashed connection between the atoms.…”
Section: Methods and Structural Analysismentioning
confidence: 99%
“…Besides, it is justified that atomistic simulations can be regarded as a tool for investigating the MT, SME, and SE by providing more structural details and 2 Advances in Materials Science and Engineering mechanistic insights at the atomic scale. For example, MD simulations exhibit a possibility of describing the phase structures derived from temperature-and stress-induced phase transformation [7,8]. In the MD method, several characteristics of phase transformation in the NiTi alloy had been revealed through a semiempirical pair potential [9].…”
Section: Introductionmentioning
confidence: 99%